Study of the Programme of Consolidation of Holdings Design, Schedules, etc. and instructions - Planning Commission (Planning Commission, 1967)
The background papers relating to the study on Consolidation of Holdings, the objectives of the study, schedules, guide Points, instructions, etc., have been prepared in the Economic Administration Division. The final form that has emerged is the result of the discussions with the officers at headquarters and the field at the seminars held at New Delhi, Hyderabad and Chandigarh. The effort that has gone into the preparation of the study would be amply rewarded if the field officers conduct the study with meticulous care and ensure that the study is completed within the stipulated time.
Programme Evaluation Organisation Planning Commission New Delhi